CD4+CD25+FOXP3+ regulatory T cells: a potential “armor” to shield “transplanted allografts” in the war against ischemia reperfusion injury - Jeyamogan, Shareni; Leventhal, Joseph R.; Mathew, James M.; Zhang, Zheng Jenny (Frontiers in Immunology, 2023)
Despite the advances in therapeutic interventions, solid organ transplantation (SOT) remains the "gold standard" treatment for patients with end-stage organ failure. Recently, vascularized composite allotransplantation (VCA) has reemerged as a feasible treatment option for patients with complex composite tissue defects. In both SOT and VCA, ischemia reperfusion injury (IRI) is inevitable and is a predominant factor that can adversely affect transplant outcome by potentiating early graft dysfunction and/or graft rejection. Restoration of oxygenated blood supply to an organ which was previously hypoxic or ischemic for a period of time triggers cellular oxidative stress, production of both, pro-inflammatory cytokines and chemokines, infiltration of innate immune cells and amplifies adaptive alloimmune responses in the affected allograft. Currently, Food and Drug Administration (FDA) approved drugs for the treatment of IRI are unavailable, therefore an efficacious therapeutic modality to prevent, reduce and/or alleviate allograft damages caused by IRI induced inflammation is warranted to achieve the best-possible transplant outcome among recipients. The tolerogenic capacity of CD4 + CD25 + FOXP3 + regulatory T cells (Tregs), have been extensively studied in the context of transplant rejection, autoimmunity, and cancer. It was not until recently that Tregs have been recognized as a potential cell therapeutic candidate to be exploited for the prevention and/or treatment of IRI, owing to their immunomodulatory potential. Tregs can mitigate cellular oxidative stress, produce anti-inflammatory cytokines, promote wound healing, and tissue repair and prevent the infiltration of pro-inflammatory immune cells in injured tissues.By using strategic approaches to increase the number of Tregs and to promote targeted delivery, the outcome of SOT and VCA can be improved. This review focuses on two sections: (a) the therapeutic potential of Tregs in preventing and mitigating IRI in the context of SOT and VCA and (b) novel strategies on how Tregs could be utilized for the prevention and/or treatment of IRI.